Chromium (VI)-induced phytotoxicity in river catchment agriculture: evidence from physiological, biochemical and anatomical alterations in Cucumis sativus (L.) used as model species. Issue 1 (2nd January 2016) - Tripathi, Ashutosh; Tripathi, Durgesh Kumar; Chauhan, D. K.; Kumar, Niraj
ABSTRACT: The present study investigates the impact of different Cr(VI) (50–200 µM) treatments on Cucumis sativus L. seedlings which is worldwide grown in river catchments. Chromium (VI) treatments showed signiﬁcant ( P  < .05) reduction in growth, photosynthetic pigments, total protein content and PSII performance, which was in concurrence with a signiﬁcant ( P  < .05) increase in the accumulation of Cr(VI) (up to 587 ± 18.19 µg Cr g −1 in roots), lipid peroxidation (MDA: up to 483%), H2 O2 (up to 453%) and O 2 − (up to 551%) compared to the control seedlings. Chlorophyll fluorescence parameters, such as F m, F v, F v / F m, F m / F 0 and F v / F 0, were declined while F 0 showed enhancements ( P  < .05). Energy ﬂux parameters, such as Phi_ E0, Psi_ 0, PIABS, declined; however, ABC/RC, ET0 /RC, DI0 /RC and TR0 /RC increased significantly ( P  < .05) under Cr(VI) treatments as compared to control. In addition, the levels of qP were reduced while NPQ was appreciably enhanced under different Cr(VI) treatments. The histochemical observations of H2 O2 and O 2 − were in accordance with their total estimation. Furthermore, Cr(VI) also severely injured the anatomical structure of roots. This study suggests that a higher accumulation of Cr(VI) in cucumber seedlings warrants serious attention in the studied catchments of the Ganges river to avoid any food contamination and biomagnifications to higher trophic levels.